Effect of different operating parameters on extraction of active compounds from pitaya peel by microwave assisted extraction (MAE) - Muhammad Azlan, Nazeri; Norashikin, Mat Zain (Penerbit Universiti Teknologi Malaysia, 2018)
Microwave-assisted extraction (MAE) has been recognised as a powerful potential alternative for the extraction of active compounds from plant materials compared to other advanced methods such as ultrasound-assisted extraction (UAE), pressurised liquid extraction (PLE), supercritical fluid extraction (SFE), and Soxhlet. The advantages of MAE processing technique are reduced processing time, higher yield, lower usage of solvent, and smaller energy demand. Nevertheless, most researchers used organic solvents which have toxic effect on the environment. Therefore, in this study, distilled water was used as a natural solvent in the sample preparation. Pitaya peel is a form of potential fruit waste, especially in the food industry. Notably, its liquid extract can be applied as natural colouring and it contains beneficial active compounds that have commercial value. Wastage during the processing of food is inevitable and disposal can be a major problem for the industry and the society. Negative impacts such as pollution to the environment, hazards to human health, and loss of income to the waste generator may occur. Thus, extraction can be an effective solution for minimising waste produced by the food processing industry. Food waste often contain several usable substances of high value including some of that are beneficial for health such as mineral contents and phenolic compounds. The aim of this research was to find the optimal operating parameters for extraction of total phenolic content (TPC) from pitaya peel using MAE method. These parameters were the (1) weight of the sample, (2) temperature, (3) power, and (4) extraction time. In this research, the results showed that the best condition for the parameters of MAE were at the power of 400 W, temperature of 45 °C, and 20 min contact time when extracting 1.2 g pitaya peel in 50 mL distilled water. These figures were validated through statistical analysis using SPSS with Bonferroni post hoc tests. The TPC presented in the liquid extract was measured in GAE/g. In addition, the Inhibitory Concentration (IC50) of the liquid extract was determined by applying the best condition for the parameters of MAE and DPPH reagent as the synthetic free radical. The IC50 value obtained in this research was 0.52 mg/mL.